Revisitando a química de chalconas biologicamente ativas : síntese, caracterização estrutural e estudo biológico - Viana, Lucas Aguiar Braga (2023)
In the present work the synthesis of twelve chalcones already known in the literature is described: (E)-1,3-di(4-hidroxifenil)prop-2-en-1-ona (R1), (E)-3-(4-metoxifenil)-1-(4-nitrofenil)-prop-2-en-1-ona (R2), (E)-3-(4-metoxifenil)-1-1(3-nitrofenil)-prop-2-en-1-ona (R3), (E)-3-(4-metoxifenil)-1-(p-toluil)-prop-2-en-1-ona (R4), (E)-3-(3-nitrofenil)-1-(p-toluil)prop-2-en-1-ona (R5), (E)-3-(4-metoxifenil)-1-fenilprop-2-en-1-ona (R6), (E)-3-(3-nitrofenil)-1-fenilprop-2-en-1-ona (R7), (E)-3-(4-hidroxifenil)-1-fenilprop-2-en-1-ona (R8), (E)-3-(3-hidroxifenil)-1-fenilprop-2-en-1-ona (R9), (E)-3-(3-hidroxifenil)-1-(4-hidroxifenil)prop-2-en-1-ona (R10), (E)-1-(4-hydroxyphenyl)-3-(4-methoxyphenyl)prop-2-en-1-one (R11) and (E)-3-(1H-indol-5-yl)-1-phenylprop-2-en-1-one (R12), via the Claisen-Schmidt condensation reaction. All compounds obtained were duly characterized by Infrared (IR), Hydrogen and Carbon-13 Nuclear Magnetic Resonance (1H NMR and 13C-APT) spectroscopic techniques. The prediction of the desired drug properties was determined by in silico study performed in Molinspiration and ADMETlab 2.0 software considering the parameters of Lipinski and Veber rules. The antimicrobial activity was determined by in vitro microbiological assay, evaluating the antifungal and antibacterial activity against ten microorganisms: three bacterial strains (Staphylococcus aureus ATCC-13150, Staphylococcus epidermidis ATCC-12228 and Pseudomonas aeruginosa ATCC-25853) and seven fungal strains (Candida albicans ATCC-76485, Candida albicans LM-70, Candida tropicalis ATCC-13803, Candida tropicalis LM-12, Cryptococcus neoformans ATCC-66031, Aspergillus flavus ATCC_4603 and Aspergillus flavus LM-55) by broth microdilution method. The chalcones were obtained with yields ranging from 34.80 to 86.15%. The data obtained from the in silico study were positive regarding drug-likeness and oral bioavailability characteristics for all molecules evaluated, with logP ranging from 2.83 to 4.32; logS from -3.132 to -5.568, with all TPSA values lower than 140 Å2, meaning good permeability for the chalcones synthesized. The data from the antimicrobial study showed that six chalcones showed inhibitory effect and six were inactive. The minimum inhibitory concentration (MIC) values ranged from 128 to 1024 μg. mL-1. The chalcones (R1), (R4) and (R6), exhibited antimicrobial activity against all ten strains tested and chalcona (R1) showed the lowest MIC of 128 μg mL-1 against most strains, except in the fungi Candida albicans LM-70, Aspergillus flavus ATCC_4603 and Aspergillus flavus LM-55 with MIC of 256 μg mL-1, representing a chalcona with potentiality for use in these microorganisms. Chalcone (R5) inhibited only five strains, all with MIC of 256 μg mL-1, proving to be more selective to bacterial strains. The chalcones (R2), (R3), (R8), (R9), (R11), (R12), showed no inhibitory effect on the growth of microorganisms including bacterial and fungal species. Although the structures are already known in the literature, it is evident the importance of the constant evaluation of new antimicrobial potentials, thus, the study indicated the potentiality of six chalcones, with emphasis on (R1) and (R4), fitting more careful analysis.